Mechanisms of effecting of surface stress on output parameters of surface acoustic wave devices - Melnychuk, Andrii (Видавництво Львівської політехніки, 2010)
In this paper reasons of surface stress are given, and interaction mechanisms of surface stresses and surface acoustic wave (SAW) parameters are described.
Keywords: surface acoustic wave parameter; SAW; surface stress